2021
DOI: 10.3389/fmolb.2021.619027
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Subtyping Reveals Immune alterations:TCGA Database for Prognosis in Ovarian Serous Cystadenocarcinoma

Abstract: Serous ovarian cancer is the most common and primary death type in ovarian cancer. In recent studies, tumor microenvironment and tumor immune infiltration significantly affect the prognosis of ovarian cancer. This study analyzed the four gene expression types of ovarian cancer in TCGA database to extract differentially expressed genes and verify the prognostic significance. Meanwhile, functional enrichment and protein interaction network analysis exposed that these genes were related to immune response and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…To avoid excessive false positive and false negative results, up-regulated differentially expressed genes (DEGs) between 2 groups were identified with the criteria of P<0.05 and fold change (FC) >3/2, down-regulated DEGs between two groups were identified with the criteria of P<0.05 and FC <2/3 according to the previous criteria ( 18 - 21 ). The ClusterProfiler package was used to conduct the Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO) enrichment analyses.…”
Section: Methodsmentioning
confidence: 99%
“…To avoid excessive false positive and false negative results, up-regulated differentially expressed genes (DEGs) between 2 groups were identified with the criteria of P<0.05 and fold change (FC) >3/2, down-regulated DEGs between two groups were identified with the criteria of P<0.05 and FC <2/3 according to the previous criteria ( 18 - 21 ). The ClusterProfiler package was used to conduct the Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO) enrichment analyses.…”
Section: Methodsmentioning
confidence: 99%
“…[ 9 , 10 ] One research reported that a better clinical prognosis model related to the immune microenvironment was established for OV. [ 11 ] Another study identified 10 immune microenvironment genes related to the prognosis of OV. [ 12 ] Besides, 2 lncRNA-related molecular subtypes which had significant different prognosis and immunological characteristics by analyzing OV cohort in The Cancer Genome Atlas (TCGA).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their previous omission, these easily assessed factors profiling the distinct specificities of functional status and social support may be prognostic indicators. Currently used prognostic models for HGSOC mainly focus on biomarkers (12)(13)(14)(15), or clinical features with radiology (16,17). They reported the range of models' c-index of about 0.6-0.7.…”
Section: Introductionmentioning
confidence: 99%